Determinants Of Retained Placenta At Malinau Hospital, North Kalimantan - Desi Marga Sinta (Journal for Research in Public Health, 2024)
Malinau Regency health profile data in 2018 recorded 268 deliveries, and 38 cases (14.1%) of them experienced retained placenta. Factors that cause retained placenta are placenta previa, caesarean section scar, repeated curettage, age, history of manual placenta, anemia, history of surgery and parity. Remaining placental remains in the uterus can cause weakened contractions which can cause postpartum bleeding. The aim of this study was to determine the determinants of the incidence of retained placenta in Malinau District Hospital, North Kalimantan.This research uses design correlational research with cross sectional approach. Respondents are recruited using accidental Sampling techniques with a sample of 36 people. Independent variables were parity and history of retained placenta. The dependent variable is incidence of retained placenta. Statistical test results using chi square.The research results showed that the majority of mothers giving birth at Malinau District Hospital had high parity, namely 23 (63.9%). The majority of mothers giving birth at Malinau Regional Hospital had a history of placental retention, 21 (58.3%), and the majority of mothers giving birth at Malinau Regional Hospital experienced placental retention, namely 25 (69.4%). The results of data analysis show that the significance level is 0.000 < α = 0.005 so that H0 rejected and H1 Thus, it is accepted that there is a relationship between parity and a history of placental retention with the incidence of retention at Malinau Regional Hospital, North Kalimantan.The conclusion in this research is mothers who have a history retained placenta and high parity tend to have a risk of retained placenta in the next delivery